Comparison of the effects of pegylated granulocyte-colony stimulating factor and granulocyte-colony stimulating factor on cytopenia induced by dose-dense chemotherapy in breast cancer patients - Farzaneh Ashrafi (Journal of Research in Medical Sciences, 2018)
Background: Myelosuppression is one of the frequent side effects of chemotherapy in breast cancer patients. Granulocyte-colony stimulating factor (G-CSF) and pegylated G-CSF are used for the prevention of neutropenia after chemotherapy. Pegylated G-CSF has longer half-life of action and can be used as a single dose in comparison to G-CSF. The aim of this study is to compare the grade of cytopenia and side effects between G-CSF and biosimilar pegylated G-CSF in breast cancer patients treated with dose-dense chemotherapy. Materials and Methods: In the cross-over clinical trial study, 24 women with breast cancer were randomly divided into two groups and treated with dose-dense chemotherapy. The first group was treated with single dose of 6 mg biosimilar pegylated G-CSF 24 h after the first course of chemotherapy and the second course was followed by 300 μg daily injection of G-CSF for 6 days. The chemotherapy regimen was combination of doxorubicin 60 mg/m2 and cyclophosphamide 600 mg/m2. The second group was treated with G-CSF after the first course and pegylated G-CSF after the second course. Cell blood count (CBC) and side effects were evaluated 1 and 2 weeks after both courses of chemotherapy. Results: In this study, no significant carryover effect and treatment effect about the CBC parameters was found between pegylated G-CSF and G-CSF. Patients who were treated with biosimilar pegylated G-CSF had significantly higher side effects such as bone pain (P = 0.09) and gastrointestinal effects (P = 0.005) in comparison to G-CSF. Conclusion: G-CSF and biosimilar pegylated G-CSF are effective in reducing cytopenia in breast cancer patients treated with dose-dense chemotherapy, but side effects induced by pegylated G-CSF (Pegagen) are higher.